(untitled) (Journal of Pharmaceutical Negative Results, 2022)
INTRODUCTION Obstructive airway diseases include Chronic obstructive airway disease, Bronchial Asthma, and Bronchiectasis. Non-Invasive ventilation is the mainstay treatment in Obstructive Lung diseases. It can reduce mortality and morbidity in patients with acute hypercapnic respiratory failure. METHODS Prospective cohort of 50 patients with Obstructive airway diseases, attending Respiratory Medicine department in Meenakshi Medical College either casualty or OP, satisfying the inclusion and exclusion criteria from December 2019 to June 2021 were taken for the study. RESULTS A total number of 50 patients were enrolled in this study out of which 15 were female and 35 were male patients which was constituted 30 and 70% respectively. In our study we compared clinical parameters like sputum consistency, smoking index with duration of NIV therapy. We compared radiological parameters like Chest X ray and Biochemical parameters like PaCO2 with duration of NIV therapy. We also analyzed that if T2DM had any influence on NIV treatment. We compared the duration of NIV with PAH based on ECG findings. CONCLUSION Obstructive airway disease with acute exacerbations should be treated ICU with ventilatory support. In the past couple of years very few studies have been conducted for predicting outcome of NIV in patients with obstructive airway disease